The endoscopy safety checklist: A longitudinal study of factors affecting compliance in a tertiary referral centre within the United Kingdom. Issue 1 (11th February 2015) - Matharoo, Manmeet; Sevdalis, Nick; Thillai, Muhunthan; Bouri, Sonia; Marjot, Thomas; Haycock, Adam; Thomas-Gibson, Siwan
Abstract: Gastrointestinal endoscopy is a widely used diagnostic and therapeutic procedure both within the United Kingdom and worldwide. With an increasingly older population the potential for complications is increased. The Wolfson Unit for Endoscopy at St. Mark's Hospital in London is a tertiary referral centre, which conducts over 14, 000 endoscopic procedures annually. However, despite this high throughput, our baseline observations were that the procedure for safety checks was highly variable. Over a seven-day period we conducted a questionnaire-based survey to all staff members involved with endoscopy within our unit. We found that there was little consensus between team members, both in terms of essential safety checks and designating responsibility for the checks. A panel of experts was convened in order to devise a safety checklist and a strategy for increasing compliance with the checklist among all staff members. Using a combination of electronic and physical reminders and incentives, we found that there was a significant increase in completed checklist (53% to 66%, p = 0.021) and decrease in the number of checklists left blank post intervention (10% to 2%, p=0.03). We believe that post implementation validation of safety checklists is an important method to ensure their proper use.